INFLUENCE OF PRODUCT DESIGN AND FOOD TASTE ON CONSUMER INTEREST IN MOMOGI SNACK PRODUCTS - Mellya Vidya Savitri, Divo; Fatkhur Romadhoni, Ita; Handajani, Sri; Gita Miranti, Mauren Gita Miranti4 (Universitas Islam Lamongan, 2024)
In the era of globalization and increasingly fierce business competition, product design is no longer only seen as an aesthetic aspect, but also as an important element that can influence consumer behavior in determining consumer decisions in purchasing a product. Apart from product design, food taste (multisensory sensation) is an important element that can influence consumer perception and purchasing interest. The aim of this research is to analyze the influence of product design and food taste on consumer buying interest. The sample used was 153 respondents who were taken using a questionnaire and using multiple linear regression analysis techniques. The results show that product design and food taste have a significant positive effect on consumer buying interest in Snack Momogi.